Interpercepção: uma arquitetura de software para compartilhamento de ambientes virtuais com interfaces gráficas distintas - Dantas, Rummenigge Rudson (2008)
In this work, we propose the Interperception paradigm, a new approach that includes a set of rules and a software architecture for merge users from different interfaces in the same virtual environment. The system detects the user resources and provide transformations on the data in order to allow its visualization in 3D, 2D and textual (1D) interfaces. This allows any user to connect, access information, and exchange information with other users in a feasible way, without needs of changing hardware or software. As results are presented two virtual environments builded acording this paradigm